Role of Pradhan Mantri Awas Yojana Project in Urban Governance of West Bengal: A Review of Beldanga Municipality (2015-2022) - Paul, Ritwik; Charmkar, Ramsiya (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
Pradhan Mantri Awas Yojana (PMAY) aims at Providing Housing for All (HFA) by 2022 in 75 years of its Independence Day. The urban homeless persons contribute to the frugality of the metropolises, and therefore the Nation, as cheap Laboure in the informal sector; yet they live with no sanctum or social security. The urban homeless is faced with numerous challenges like no access to abecedarian Public Services similar as health, education, food, water and sanitation. Pradhan Mantri Awas Yojana (PMAY) also aims at furnishing a pucca house to every family with water connection, restroom installations, 24 X 7 electricity force and access. The Mission seeks to address the casing demand of urban poor including slum resides through" In Situ" Slum Redevelopment, Affordable Housing through credit linked subvention, Affordable casing in cooperation and subvention for devisee led individual house. Under the charge, heirs can take advantage under one element only. Beldanga Municipality takes one vertical for perpetration of the design i.e." Beneficiary- led- construction". For this design, Beldanga Municipality conducted Demand Assessment check for getting total demand of houses in the ULB. From this check, the total check form entered 3322 for" Beneficiary- led- Construction". Out of this, 1594 form entered from 44 slums and 1728 forms entered from non-slums. These houses will be constructed through" Beneficiary- led- Construction". still, for perpetration in the fourth plan period, i.e. 2019- 20, the megacity, through reflections, has decided to consider only 929 heirs, under Beneficiary led construction, across all 14 wards including slum and non-slum homes. In this phase 475 no. of slums & 454 non-slum pockets have been named. The total design estimate for construction of dwelling units, including provision of structure for 929 homes under Beneficiary- Led- Construction is Rs. 3760.59 Lakhs.